2016
DOI: 10.1212/wnl.0000000000002469
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis prevalence in the United States commercially insured population

Abstract: MS prevalence rates from a representative commercially insured database were higher than or consistent with prior US estimates. For further accuracy improvement of US prevalence estimates, results should be confirmed after validation of MS identification algorithms, and should be expanded to other US populations, including the government-insured and the uninsured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
132
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(141 citation statements)
references
References 21 publications
6
132
0
3
Order By: Relevance
“…Incidence and prevalence rates in our study are within the range of a similar study from 2000 in Germany (Hein: 2000tm) and of several recent studies across Europe and the United States [9,10,11]. In contrast, earlier studies tend to report lower incidence and prevalence [1] figures [12].…”
Section: Discussionsupporting
confidence: 82%
“…Incidence and prevalence rates in our study are within the range of a similar study from 2000 in Germany (Hein: 2000tm) and of several recent studies across Europe and the United States [9,10,11]. In contrast, earlier studies tend to report lower incidence and prevalence [1] figures [12].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, MS incidence and prevalence are not consistently reported or tracked in the U.S." 19 Currently used estimates are 350,000 to 500,000 individuals with MS in the United States 14 ; these estimates are likely low because a recently published study indicated more than 400,000 individuals with MS in the United States who have commercial insurance and did not include individuals with Medicare, Medicaid, or other forms of public insurance. 20 Based on our projections of the capacity for neurologist visits, the 350,000 to 500,000 MS prevalence estimate corresponds to four to six neurologist visits per patient per year.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system, affecting an estimated 450,000 to 550,000 people in the United States [1,2]. The financial burden accompanying MS is a central component of the disease experience, ranking second among all chronic conditions in direct costs behind congestive heart failure [3].…”
Section: Introductionmentioning
confidence: 99%